Sociodemographic and clinical factors associated with contraceptive choice in postpartum women in San José Hospital 2024 - Acorda Ochoa , Sandra Melisa (2025)
Introduction: Postpartum contraception promotes sexual and reproductive health, yet barriers to timely access persist. Objective: To identify sociodemographic and clinical factors associated with contraceptive choice among postpartum women at Hospital San José. Methods: A cross-sectional analytical study was conducted in 2024 with 341 postpartum women aged ≥18 years at Hospital San José (Callao, Peru), all of whom received prior contraceptive counseling. Sociodemographic and clinical variables were assessed through medical record review. Bivariate analysis (chi-square test) and Poisson regression with robust variance were applied. Statistical significance was set at p<0.05. Results: Among participants, 82.7 % were under 35 years of age, 53.7 % had secondary education, and 44.6 % were cohabiting. The most commonly used method was the three-month injection (28.7 %). Vaginal delivery occurred in 69.5 % of cases. Only mode of delivery showed a statistically significant association with the use of hormonal methods, which were more frequent among women with vaginal delivery (aPR: 0.75; 95 %CI: 0.63–0.90; p=0.002). No associations were found with age, education level, marital status, parity, or clinical history. Conclusions: Mode of delivery was associated with contraceptive choice, underscoring its clinical relevance in immediate postpartum decision-making.